Legitimating war by victimization: state-corporate crime and public opinion - Klein, Josh (Crime, law and social change, 2011)
This article argues that the ideological use of victimization helps legitimate the state-corporate crime of aggressive war. This contributes to the emerging criminology of war by offering a theoretical framework to better understand how state and corporate actors legitimate criminal military action. We argue that politicians and other elite figures promote a sense of national victimization that is amplified by the news media. We partially test our theory by measuring the association between the incidence of terror victimization ideas in the news and public support for the U.S. "war on terror." We find some evidence of relationships between our Terrorism Victimization Index and both victimization worry and aggressive war support.